2022
DOI: 10.3390/ani12151986
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Traits of Growing Meat Goats Fed Different Levels of Hempseed Meal

Abstract: Hempseed meal (HSM) is the byproduct of hemp seeds and is rich in crude protein and fiber, making it an ideal candidate as a feedstuff for ruminants. The objective of the present study is to evaluate the effects of feeding different levels of HSM on the carcass traits of crossbred Boer goats. Forty castrated goat kids (approximately six months, 25.63 ± 0.33 kg) were assigned to one of four treatments (n = 10) in a completely randomized design. Goats were fed pelleted diets (50% forage and 50% concentrate) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Similar findings were reported by [ 31 , 34 ]. In addition, Gurung et al [ 35 ] observed no adverse effects on carcass characteristics when goats were fed a 30% hemp seed diet.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by [ 31 , 34 ]. In addition, Gurung et al [ 35 ] observed no adverse effects on carcass characteristics when goats were fed a 30% hemp seed diet.…”
Section: Discussionmentioning
confidence: 99%